In-depth exploration of postpartum hemorrhage risk factors through interviews with healthcare workers in Hospitals - Erawati, Sintya; Baroya, Ni'mal; Tri Herawati, Yennike; Martiana Wati, Dwi; Permatasari, Elok (International Journal of Health Science and Technology, 2025)
Postpartum hemorrhage (PPH) is one of the major obstetric complications responsible for approximately 75% of maternal deaths globally, particularly in low-income countries. This condition not only increases maternal morbidity and mortality but also contributes to higher needs for blood transfusion, prolonged hospitalization, and greater healthcare burden. The incidence of PPH at Dr. Soebandi Regional Hospital, Jember, reached 27%, the highest among other delivery complications in the regency. This study aimed to analyze the risk factors associated with PPH. An analytic hospital-based case-control study was conducted from January to November 2021 involving 88 mothers with PPH and 88 mothers without PPH based on medical records from 2018–2019. Antenatal factors included maternal age, anemia, birth interval, parity, and history of PPH, while intrapartum factors consisted of chorioamnionitis, labor induction, duration of labor, episiotomy, and delivery method. Data were analyzed using chi-square and logistic regression tests with a significance level of α=0.05. The results showed that maternal age >35 years (OR=4.7; 95%CI:2.35–9.82), anemia, and previous history of hemorrhage were significant risk factors. Chorioamnionitis, labor induction, and episiotomy also increased the risk, while cesarean delivery was protective (OR=0.19; 95%CI:0.08–0.45). Prevention efforts should focus on promoting pregnancy at a healthy reproductive age, improving adherence to iron supplementation, and strengthening the quality of delivery services in healthcare facilities.